SOME ENVIRONMENTAL EFFECTS ON PRODUCTIVE PERFORMANCE OF NILI- RAVI BUFFALOES IN AZAD KASHMIR - Z. Hussain; K. Javed; S.M.I. Hussain; G. S. Kiyani (Journal of Animal and Plant Sciences, 2006)
A total of 376 Performance records of 109 Nili-Ravi buffaloes maintained at Livestock Development Research Centre, Raroo, Muzaffarabad, Azad Kashmir, during 1989-2003 were utilized for the evaluation of some environmental factors affecting 305-day milk yield, lactation length and dry period. The least squares means for 305-day milk yield was 2191.858+35.553 Kg. The effect of year and season of calving and parity was significant (P<0.01) on the trait. The least squares means for lactation length was 369.53+8.44 days. The effect of year and season of calving on lactation length was significant (P<0.01), while a non-significant effect of parity on the trait was observed in this study. The least squares means for dry period was 194.4+12.37 days. Dry period was significantly influenced by season and year of calving, while the effect of parity on dry period was non-significant in the present study.
Keywords: Nili Ravi buffaloes; Azad Kashmir; Productive performance